French Roast: Consumer Response to International Conflict—Evidence from Supermarket Scanner Data - Pandya, Sonal S.; Venkatesan, Rajkumar (The Review of Economics and Statistics, 2016)
Do consumers boycott in response to international conflict? We show that during the 2003 U.S.-France dispute over the Iraq War, the market share of French-sounding, U.S. supermarket brands declined. The dispute was a negative shock to U.S. consumers’ associations with France. French-sounding brands, which consumers perceive to be French imports but are not, allow us to isolate the dispute’s effect on economic behavior, as these brands’ only link to France is through consumers’ associations. Our estimates, derived from a nationwide sample of weekly supermarket sales for over 8, 000 brands, are robust to a variety of alternate explanations. We also show that supermarkets with a higher proportion of customers who are U.S. citizens (i.e., who more strongly identify with the U.S. national identity) exhibited sharper boycotts.